Interconnection and sharing through webservices - De Giusti, Marisa Raquel (2007)
Webservices technology is one of the stilts on which the concept WEB 2.0 is sustained. This technology allows to send information between computers connected to the network, providing a high portability level communication mechanism that permits this interconnection to be made between different hardware platforms and internal data representation, many operative systems, applications developed in several languages or databases and mainly, a very simple language, standardized and efficient for information transport such as XML.